Ai confini d'Europa Italia ed Irlanda tra le due guerre - Chini, Chiara (Premio Ricerca «Città di Firenze», 2016)
Investigating the contacts between Italians and Irish over the decades separating the two world wars is like opening a small Pandora's box, creating a lively and unexpected portrait of the great number of political and cultural exchanges between two countries. Italy has always been an important cultural and spiritual reference point for Ireland; Ireland, on the other hand, has exerted a particular appeal among the Italians, appearing as a distant and mysterious place, a country of saints and heroes. Two geographically distant yet culturally close nations, whose plurality of relationships are interesting to investigate and deepen. This work brings to light an unexpectedly rich picture of a small world of passions and entanglements, of patriotism and opportunism, uniting two countries which have always been tormented by the same complex: being on the edge of political games in Europe.